Advances in Targeted Drug Delivery in Melanoma - Gowtham, Pemula (Asian Pacific Journal of Cancer Biology, 2021)
Cancer remains a major killer of mankind. Failure of conventional chemotherapy has resulted in recurrence and development of virulent multi drug resitant (MDR) phenotypes adding to the complexity and diversity of this deadly disease. Melanoma is the most aggressive and dangerous type of skin cancer, but its molecular mechanisms remain largely unclear Drug delivery systems (DDS) such as lipid- or polymer-based nanoparticles can be designed to improve the pharmacological and therapeutic properties of drugs administered parenterally with the emergence of nanotechnology, the use of nano-carriers is widely expected to alter the landscape of melanoma treatment multifunctional nanoparticles that can integrate various key components such as drugs, genes, imaging agents and targeting ligands using unique delivery platforms would be more efficient in treating cancers. This review presents some of the important principles involved in development and novel methods of treating cancers using multifunctional-targeted nanopicles. Illustrative examples of nanoparticles engineered for drug/gene combination delivery and stimuli respnsive nanoparticle systems for cancer therapy are also discussed.